Business Model for an Ehealth Monitoring System: RO-Smartageing Case Study - Maria GHEORGHE-MOISII; Monica BARBU; Cristian PETRACHE (Communications of International Proceedings, 2021)
The process of creating value through an innovative business model is able to turn an idea into a successful project. Technological development facilitates the finding of resources on the market for a progressive materialization of the value creation process. A customer-centric approach to the business segment helps entrepreneurs and innovators achieve viable solutions. The case study reveals the business model of a real eHealth monitoring system, which facilitates the autonomy and safety of the elderly at home. The research undergone within this paper has identified the main actors of the business model - exploring the different interactions between them based on the Canvas business model. The proposed value of the system determines a real benefit for customers, as well as an appropriate revenue stream. The paper contributes to the understanding of the business model and how digital technologies facilitate innovation.
Keywords: Business model; Canvas business model; eHealth monitoring system; value proposition.